Agripreneurship: A Tool for Revitalising and Unlocking Potentials of Rural Economies in India - Swetha. B; Leela Krishna Chaithanya; Subhash Kumar Saurav (Archives of Current Research International, 2025)
Agripreneurship could potentially be used as an instrumental means to address issues like low productivity, fragmented landholdings, and uncertain markets in India’s agricultural industry. Combining entrepreneurship and agriculture, agribusiness encourages creative, sustainable methods that boost resilience, productivity, and profitability. It includes a variety of pursuits that promote rural development, food security, and environmental preservation, such as organic farming, agro-processing, and agritourism. The expansion of agripreneurship has been propelled by important factors such as market orientation, legislative assistance, and technological adoption, which have reduced urban migration and created opportunities. This article also addresses issues like low technical awareness, financial limitations, and inadequate infrastructure faced by agripreneurs. Agripreneurship offers an avenue to economic growth, poverty reduction, and improved livelihoods by encouraging innovation, capacity building, and sustainable practices. Further successful case studies highlight agripreneurship’s capacity to stimulate rural economies, and appropriate policies and institutional measures were suggested to facilitate its extensive adoption. This represents an enormous shift in India’s agricultural landscape.